2023
DOI: 10.1007/s00423-023-02934-0
|View full text |Cite
|
Sign up to set email alerts
|

Early closure compared to late closure of temporary ileostomy in rectal cancer: a randomized controlled trial study

Hadi Ahmadi-Amoli,
Mohsen Rahimi,
Raziyeh Abedi-kichi
et al.

Abstract: A temporary loop ileostomy is one of the most common methods for the prevention of anastomotic leakage in rectal cancer patients who underwent low anterior resection. However, the optimal timing of loop ileostomy reversal remains unknown. The main purpose of this study is to assess the suitable time for a reversal of temporary loop ileostomy in rectal cancer patients. MethodsWe conducted a prospective, randomized trial at Sina Hospital, Tehran, Iran from 2020 to 2021 to determine the appropriate time for closu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Li et al [ 28 ] reported that early reversal of the ileostomy before 3 months was both practical and safe, allowing sufficient time to recover from the initial resection and soften intra-abdominal adhesions. Ahmadi-Amoli H et al[ 29 ] concluded that early reversal of ileostomy was not better than late reversal, and there was no significant difference between the two groups in reducing the risk of stoma complications. There were significant differences in the reported risk factors for complications after stoma reversa and no studies have analyzed the risk factors for stoma-related complications and overall postoperative complications separately.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 28 ] reported that early reversal of the ileostomy before 3 months was both practical and safe, allowing sufficient time to recover from the initial resection and soften intra-abdominal adhesions. Ahmadi-Amoli H et al[ 29 ] concluded that early reversal of ileostomy was not better than late reversal, and there was no significant difference between the two groups in reducing the risk of stoma complications. There were significant differences in the reported risk factors for complications after stoma reversa and no studies have analyzed the risk factors for stoma-related complications and overall postoperative complications separately.…”
Section: Introductionmentioning
confidence: 99%